Being Mindful: A Long-term Investigation of an Interdisciplinary Course in Mindfulness - Sarah Ellen Braun MS; Patricia Kinser PhD, WHNP-BC, RN; Caroline K Carrico PhD; Alan Dow MD, MSHA (SAGE Publishing, 2019)
Background Burnout and work-related stress in health-care professionals (HCPs) is a growing concern to the optimal functioning of the health-care system. Mindfulness-based interventions may be well-suited to address burnout in HCPs. Objective The purpose of this study was (1) to quantitatively evaluate the effect of a mindfulness-based intervention for interdisciplinary HCPs over time and at a long-term follow-up and (2) to explore perceived benefits, facilitators, and barriers to the practice of mindfulness at the long-term follow-up. Design A mixed-method, repeated measures, within-subjects design was used to investigate Mindfulness for Interdisciplinary HCPs (MIHP) at baseline, post-MIHP, and a follow-up (6 months to 1.5 years after MIHP). MIHP is an 8-week, group-based course for interdisciplinary HCPs and students, with weekly meditation training, gentle yoga, and discussions on the application of mindfulness to common stressors faced by HCPs. Main outcome measures were the Maslach Burnout Inventory-Health Services Survey and the Five Facet Mindfulness Questionnaire. A semistructured interview was used to explore participants' perceptions of sustained effects and practice in the context of HCP work at the long-term follow-up. The study protocol was registered with ClinicalTrials.gov (NCT02736292). Results Eighteen HCPs (88% female) participated in the study. Significant reductions were found after the intervention for 2 subscales of burnout: depersonalization, F (2, 17) = 5.98, P  = .01, and emotional exhaustion, F (2, 17) = 2.64, P  = .10. Three facets of dispositional mindfulness showed significant increases at long-term follow-up, act aware: F (2, 15) = 4.47, P  = .03, nonjudge: F (2, 15) = 4.7, P  = .03, and nonreactivity: F (2, 15) = 3.58, P  = .05. Continued practice of skills long term was facilitated by the use of informal practice and perceived improvement in work and personal life. Conclusion In sum, MIHP improved subscales of burnout and mindfulness. These findings should be further explored with a larger, controlled study. Interventions should focus on developing mindfulness practice that can be integrated into the work of HCPs.